Tingkat Tutur dalam Bahasa Sasak dan Bahasa Jawa - Wilian, Sudirman (Wacana, Journal of the Humanities of Indonesia, 2006)
This paper discusses about speech levels in Sasak, the language of the indigenious people of the island of Lombok, examining the style, meaning and some historical background of the speech levels. Based on the data, it shows that Sasak, like Javanese and Balinese, also contains low, mid, high and few honorific vocabularies which are assumed to have been borrowed from Javanese (Steven, 1975; Nothofer, 1975). However, the use of the high and honorific variations are scarecly heard in the everyday common Sasaks conversation. In most occurrences, the high speech level is pronounced only among the so called menak Sasaks and its surrounding. Therefore, it rejects the idea that Sasak speech levels is as elaborate and complex as Javanese due to the fact that Sasak has only a few high and honorific vocabularies known by the Sasak aristocracy.